The amended EIA directive creates opportunities for public health. (13th November 2019) - Cave, B; Mekel, O; Nowacki, J; Silva, F; Xiao, Y; Claßen, T h; Martin-Olmedo, P
Abstract: Environmental Impact Assessment (EIA) is conducted by the developer as part of the process of seeking consent to proceed with the project. The developer may be a public authority or a private company. The Directive for Environmental Impact Assessment (EIA) (2011/92/EU) was amended in 2014 (2014/52/EU). The changes are now transposed into national regulations across European Union Member States. These changes have an influence beyond EU borders, for example, through the policies of the European Investment Bank and the European Bank of Reconstruction and Development. The amendments to the Directive create both opportunities and challenges for public health. The opportunities stem from the changes that have been made to the Directive. Population and human health are now on the list of core topics that must be considered in an EIA. The other core topics to be assessed are each 'determinants of health', for example: biodiversity; land, soil, water, air and climate; and material assets, cultural heritage and the landscape. The Directive now requires the interaction between these factors to be considered. The amended Directive includes other issues that are relevant to human health, for example, climate change and vulnerability (exposure and resilience) to major accidents and/or disasters. The developer's assessment must be prepared by Competent Experts. The changes also pose challenges. These are technical. For example, human health needs to be assessed within the framework of EIA. The changes also pose challenges to the public health workforce. There is a need to ensure there is capacity to participate in EIA. The EIA is typically prepared by the developer and reviewed by the competent authority. There is a role for public health expertise in these complementary activities. This presentation will focus on the opportunities created by the changes to the Directive and the opportunities this creates. It will also touch on the challenges.